Quality of Life of Post-Mastectomy Women Living in a Semi-Arid Region of Brazil - Araújo Neto, Emídio A. (Int J Environ Res Public Health, 2017)
Health is the major reference regarding quality of life; when it comes to breast cancer in particular, the loss of a breast traumatically affects a woman’s life, reflecting on her quality of life. Recognizing this problem, our aim was to investigate the quality of life of women who live in a semi-arid region of Brazil after breast cancer mastectomy. In this exploratory, transversal and observational study, a Brazilian variantof the shorter version of the original instrument from the World Health Organization Quality of Life (WHOQOL-BREF), applied in the study population, was analyzed and their socio-demographic profile was obtained. The sample was composed of 50 mastectomized women. The 50 included patients comprised women at a mean age of 54 years. Most of them had finished elementary school, and their average income was one Brazilian minimum monthly wage. Regarding the data related to quality of life, the highest score was found in the social relationships domain (4.29) followed by the psychological (4.09) and environmental (3.88) domains. The lowest score observed was for the physical domain (3.48). With these findings we can say that social and psychological parameters are driving factors of the quality of life in post-mastectomy women. Therefore, these results are useful to establish strategies to improve the quality of life of breast cancer mastectomy patients.